2020
DOI: 10.1186/s40168-020-00904-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle treatment of maize analyzed through the metatranscriptome: compromised nitrogen cycling, possible phytopathogen selection, and plant hormesis

Abstract: Background The beneficial use of nanoparticle silver or nanosilver may be confounded when its potent antimicrobial properties impact non-target members of natural microbiomes such as those present in soil or the plant rhizosphere. Agricultural soils are a likely sink for nanosilver due to its presence in agrochemicals and land-applied biosolids, but a complete assessment of nanosilver’s effects on this environment is lacking because the impact on the natural soil microbiome is not known. In a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Abundance of Acidobacteria is positively correlated with the availability of organic carbon and disease suppression [ 62 ] . Sillen et al [ 63 ] observed that application of nanosilver increased the abundance of bacterial groups such as Bacteroidetes and Acidobacteria , which are widely recognized for their biocontrol potential, and decreased the population of Planctomycetes and Actinobacteria . Similarly, Kibby and Strevett [ 64 ] also reported that application of sulphate modified polystyrene nanomaterial increased the rhizospheric microbial population.…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of Acidobacteria is positively correlated with the availability of organic carbon and disease suppression [ 62 ] . Sillen et al [ 63 ] observed that application of nanosilver increased the abundance of bacterial groups such as Bacteroidetes and Acidobacteria , which are widely recognized for their biocontrol potential, and decreased the population of Planctomycetes and Actinobacteria . Similarly, Kibby and Strevett [ 64 ] also reported that application of sulphate modified polystyrene nanomaterial increased the rhizospheric microbial population.…”
Section: Discussionmentioning
confidence: 99%
“…Compromised nitrogen cycling, possible phytopathogen selection, and plant hormesis effects were detected via metatranscriptome analysis. In the long term, this could turn out to be negative to crop productivity and ecosystem health [ 130 ].…”
Section: Hormesis Effects In Plantsmentioning
confidence: 99%
“…Given that AgNPs are a wide-spectrum bactericide, non-target members of the soil microbiome could be negatively impacted by AgNP exposure. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…Given that AgNPs are a wide-spectrum bactericide, nontarget members of the soil microbiome could be negatively impacted by AgNP exposure. 17,18 In order to answer these questions, a long-term (120 days) life cycle study was conducted in which rice plants were grown in soil at realistic doses (0, 1, and 10 mg kg −1 ). The impacts of AgNPs on rice yield and grain quality were evaluated.…”
Section: Introductionmentioning
confidence: 99%